THE CONSTRUCTION OF THE POST-REVOLUTIONARY STATE IN MEXICO. AN APPROACH FROM THE PUBLIC ADMINISTRATION - Uhthoff López, Luz María (2019)
This article examines the changes in the structure of the post-revolutionary public administration. Special interest is placed in the figure of the departments, dependencies not sufficiently studied in historiography, but which were part of the new administrative configuration, fulfilling relevant functions in the new postrevolutionary public policies. Although for the State it was a priority to address the financial problems and demands of the army during the first years after the Revolution, in the following stages public policies amplified and diversified their functions directed towards the population, trying to meet social demands and increase their influence in the economy in order to strengthen its hegemony. Thus, the public administration is a privileged vantage point to understand the construction of the post-revolutionary State.